Keberlakuan Yuridis Peraturan Protokol Kesehatan di Provinsi Bali - I Gede Mallik Satya Devangga; I Nyoman Putu Budiartha; Ida Ayu Putu Widiati (Fakultas Hukum, Universitas Warmadewa, 2021)
The increase in Covid-19 caused the Bali provincial government to issue Bali governor regulation number 46 of 2020 which is an order from presidential instruction number 6 of 2020. Presidential instruction is not a product of statutory regulations, the researchers formulated two research objectives, namely to determine the position of Bali governor regulation number 46 2020 concerning the implementation of discipline and enforcement of health protocol laws as an effort to prevent and control the 2019 coronavirus disease in a new era of life in the statutory system in Indonesia, as well as to determine the validity of the enactment of the Bali governor's regulation Number 46 of 2020 in the statutory system of law in Indonesia. Indonesia The research method used in this study is a normative juridical research method. Based on the results of the research, it can be argued that Bali governor regulation number 46 of 2020 is the implementing regulation of the presidential instruction as a product of policy regulations. Then, Bali Governor regulation Number 46 of 2020 does not have binding power as is the case with statutory regulations. the basis for the judge's consideration is not statutory regulations but the general principle of good governance.